Demystifying the Flow: Biocatalytic Reaction Intensification in Microstructured Enzyme Reactors. Issue 3 (28th August 2018) - Bolivar, Juan M.; Valikhani, Donya; Nidetzky, Bernd
Abstract : Continuous (flow) reactors have drawn a wave of renewed interest in biocatalysis. Many studies find that the flow reactor offers enhanced conversion efficiency. What the reported reaction intensification actually consists in, however, often remains obscure. Here, a canonical microreactor design for heterogeneously catalyzed continuous biotransformations, featuring flow microchannels that contain the enzyme immobilized on their wall surface are examined. Glycosylations by sucrose phosphorylase are used to assess the potential for reaction intensification due to microscale effects. Key variables are identified, and their corresponding relationship equations, to describe, and optimize, the interplay between reaction characteristics, microchannel geometry and reactor operation. The maximum space‐time‐yield ( STY_max ) scales directly with the enzyme activity immobilized on the available wall surface. Timescale analysis, comparing the characteristic times of reaction ( τ reac ) and diffusion ( τ diff ) to the mean residence time ( τ res ), reveals operational conditions for optimum reactor output. Theoretical insight into determinants of microreactor performance is applied to biocatalytic syntheses of α‐d ‐glucose 1‐phosphate and α‐glucosyl glycerol. Process boundaries for enzyme showing, respectively, high (80 U mg −1 ) and low (4 U mg −1 ) specific activities are thus established and options for process design revealed. Opportunities, and limitations, of the application of principles of microscale flow chemistry to biocatalytic transformations are made evident. Abstract : The assessment of the potential of flow microreactors for reaction intensification in biocatalysis is shown. A general framework is presented analysis of a wall‐immobilized enzyme microreactor, and the interplay is revealed between reaction/enzyme characteristics ( A imm, η ), microchannel geometry ( L ) and reactor operation ( D ) in defining reactor output ( X, P out, STY ). Analysis is exemplarily applied to syntheses of α‐D‐glucose 1‐phosphate and α‐glucosyl glycerol. Opportunities, and limitations, of the application of microscale flow chemistry to biocatalytic transformations are made evident.